Juridical Analysis of the National Inquiry of the Nation Human Rights Commision in Guaranteeing the Constitutional Existence of the Rights of Customary Law Communities to Customary Forest Areas - M. Yusup Febrian (Fakultas Hukum Dehasen, 2023)
The National Inquiry on the Juridical Analysis of the National Commission on Human Rights (Komnas HAM) aims to ensure the constitutional existence of the rights of customary law communities over customary forest areas. The inquiry focuses on the rights of customary law communities over their territories in forest areas. The first book of the inquiry report, entitled